High‐maturity levels: achieving CMMI ML‐5 in a consultancy company. Issue 9 (31st July 2014) - Grossi, Lucas; Calvo‐Manzano, Jose A.; San Feliu, Tomas; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT Most organizations that use the Capability Maturity Model Integration (CMMI) stop their process improvement journey at Maturity Level 3 or less. The discussion about CMMI high‐maturity levels has always been controversial, going most of the times through the consideration of return of investment, provider selection, and interpretation issues. Achieving Level 5 is not an easy task; it derives a lot of steps during the way. This article will show an example of the implementation of Level 5 in a consultancy company in two constellations: development and service. It depicts the example in steps, to help the understanding of the whole process. Copyright © 2014 John Wiley & Sons, Ltd.